2017
DOI: 10.1007/s00330-016-4726-3
|View full text |Cite
|
Sign up to set email alerts
|

Practical use of visual medial temporal lobe atrophy cut-off scores in Alzheimer’s disease: Validation in a large memory clinic population

Abstract: ObjectiveTo provide age-specific medial temporal lobe atrophy (MTA) cut-off scores for routine clinical practice as marker for Alzheimer’s disease (AD).MethodsPatients with AD (n = 832, mean age 81.8 years) were compared with patients with subjective cognitive impairment (n = 333, mean age 71.8 years) in a large single-centre memory clinic. Mean of right and left MTA scores was determined with visual rating (Scheltens scale) using CT (0, no atrophy to 4, severe atrophy). Relationships between age and MTA score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 40 publications
7
38
0
2
Order By: Relevance
“…"after" (n = 125) from using VRS would be greater in this group [30,31]. It cannot be excluded that an older study population or a memory clinic population would have yielded a higher prevalence of abnormal findings where a different compliance with our template cannot be excluded.…”
Section: Discussionmentioning
confidence: 89%
“…"after" (n = 125) from using VRS would be greater in this group [30,31]. It cannot be excluded that an older study population or a memory clinic population would have yielded a higher prevalence of abnormal findings where a different compliance with our template cannot be excluded.…”
Section: Discussionmentioning
confidence: 89%
“…While T1/T2 might affect atrophy ratings, a situation that the neuroradiologist is accustomed to and takes into account during ratings, field strength is not found to affect atrophy ratings [ 52 ]. Another MRI-related limitation was that the cut-offs used were based on only a single study, however, the cut-offs have been validated in several later studies [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a more-recent study that applied Scheltens' scale to computed tomography (CT) images, the authors suggested using cutoff scores of >1.5 for those aged <75 years and ≥2 for those aged >75 years. 19 In another study, Pereira et al 12 concluded that an MTA VRS score of ≥2 (in at least one hemisphere) was considered abnormal for subjects aged <75 years, whilst a score of ≥3 (in at least one hemisphere) should be considered abnormal for subjects aged >75 years. Our study findings of cutoff scores of ≥2 for those aged 70–79 years and ≥3 for those aged 80–89 years are comparable to both of these previous studies.…”
Section: Discussionmentioning
confidence: 99%